Cross-sensitization to Artemisia and Ambrosia pollen allergens in an area located outside of the current distribution range of Ambrosia - Grewling, Łukasz; Jenerowicz, Dorota; Bogawski, Paweł; Smith, Matt; Nowak, Małgorzata; Frątczak, Agata; Czarnecka-Operacz, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
Introduction : The role of long-distance transported (LDT) Ambrosia pollen in inducing new sensitization and affecting sensitization rates in Artemisia -sensitized patients is unclear. Aim : The aim of this study was to estimate the degree of cross-sensitization to Ambrosia / Artemisia allergens in citizens of Poznan (Western Poland). This area is covered by extensive Artemisia populations but does not currently have local Ambrosia populations. Material and methods : Sera of 119 patients were tested by fluoroenzyme immunoassay (CAP-FEIA system) against pollen allergen extracts of Artemisia vulgaris and Ambrosia artemisiifolia , an allergenic component of A. vulgaris (nArt v 1), and an allergenic component of A. artemisiifolia ( nAmb a 1 ). Skin prick tests (SPTs, n = 86) were performed with pollen allergen extracts of A. vulgaris and A. artemisiifolia . Artemisia and Ambrosia pollen in ambient air was collected (1996–2013) by a Hirst type volumetric trap sited at roof level (33 m). Results : The SPT showed that the prevalence of sensitization to Ambrosia and Artemisia pollen exceeded 3.5%, and 10.5%, respectively. The measurements of IgE in blood serum (CAP-FEIA) revealed that among Ambrosia -sensitized patients 90.1% (20/22 patients) were concomitantly sensitized to Artemisia . 59.1% (13/22) of these patients reacted to nArt v 1, suggesting primary sensitization to Artemisia pollen. Only 2 (9.1%) patients were mono-sensitized to Ambrosia pollen extract, but surprisingly not to nAmb a 1 . Conclusions : The LDT Ambrosia pollen had a negligible effect on the rate of sensitization to Ambrosia allergens in Poznan and did not increase the prevalence of sensitization to Artemisia pollen in this region. However, the majority of patients showing hypersensitization to Artemisia pollen might also present symptoms during elevated episodes of LDT of Ambrosia pollen.